Homework_Set_3_Solution

Homework_Set_3_Solution - Homework 3 Solutions October 12,...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Homework 3 Solutions October 12, 2005 1 Apostol page 45, problem 12: a) 1 k ! k- 1 Y r =0 n- r n = 1 k ! n ( n- 1) ... ( n- ( k- 1)) n.n.....n = n ! k !( n- k )! 1 n k Therefore 1 + n X k =1 1 k ! k- 1 Y r =0 1- r n ! = 1 + n X k =1 n ! k !( n- k )! 1 n k = 1 + n ! 1 n + n ! 2!( n- 2)! 1 n 2 + ... + 1 n n = 1 + 1 n n . b) 1 + 1 n n > 1 + n ! 1 n 2 . Now 1- r n 1 so k- 1 Y r =0 1- r n < 1 and therefore 1 + 1 n n < 1 + n X k =1 1 k ! . Also 1 k ! 1 2 k- 1 1 for all k 1, so n X k =1 1 k ! < n X j =0 1 2 j < 2 Therefore 1 + n X k =1 1 k ! < 3 2 Let k = n + 1: lim k ( k- 1) 3 k 3 = k 3- 3 k 2 + 3 k- 1 k 3 = 1- 3 k + 3 k 2- 1 k 3 Now we know that 1 k 0 as k and therefore- 3 k 0 as k . Using comparison of sequences with 1 k , we see that 3 k 2 and 1 k 3 also 0 as k . Therefore, (1- 3 k + 3 k 2- 1 k 3 ) 1 as k . And so lim n n 3 ( n + 1) 3 = 1 ....
View Full Document

Page1 / 4

Homework_Set_3_Solution - Homework 3 Solutions October 12,...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online